Relationship between self awareness and self adjustment of students with single parent - Fernanda, Suci Dwi; Taufik, Taufik (Universitas Negeri Padang, 2022)
This research is motivated by the presence of students who have single parent parents, tend to experience difficulties in learning and social relations, and show alienating behavior. This study aims to: (1) describe the self awareness of students who have single parent parents, (2) describe the adjustment of students who have single parent parents, and (3) examine the significance of the relationship between self awareness and self adjustment of students who have single parent parents. This research uses a quantitative approach with a descriptive research type. The population of this study were students with single parents at SMAN 1 Pasaman. The instruments used were the self-awareness questionnaire and the self-adjustment questionnaire. Data were analyzed using descriptive statistical techniques and Pearson Product Moment techniques to determine the relationship between self awareness and self-adjustment through the SPSS 25 statistical program. The results of the study revealed that most (62.3%) students who came from single parents had a low level of self-awareness. Furthermore, most (58.4%) students with single parents also have a low level of adjustment. There is a significant positive relationship between self-awareness and self-adjustment of students who have single parents of 0.986 with a significance level of 99%. Thus it means that the lower the level of self-awareness, the lower the self-adjustment of students will be and vice versa. Based on the research findings, guidance efforts are needed by school counselors to increase the self-awareness of students from single parents in order to improve their adjustment to learning at school. Guidance and counseling services can be carried out through information services, orientation and group guidance services.